ANALISIS PENGARUH SOSIAL MEDIA INSTAGRAM, KUALIATAS PELAYANAN JASA KONSULTAN PAJAK, DAN KESADARAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PADA KLIEN KANTOR KONSULTAN PAJAK NANANG HERMANTO - Nur Azizah; Ike Kusdyah Rachmawati; Moh. Maskan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of Instagram social media, tax consultant service quality, and tax awareness on taxpayer compliance among clients of the Nanang Hermanto Tax Consultant Office. The method used was a quantitative approach with a causal associative research design. Data collection was conducted through questionnaires distributed to 44 respondents, who were individual taxpayer clients. The analysis results indicate that partially, the variables of social media and service quality do not significantly influence taxpayer compliance. However, tax awareness has a positive and partially significant effect on taxpayer compliance. Simultaneously, these three variables significantly influence taxpayer compliance, contributing 53.7%, while the remainder is influenced by other factors outside this study. This study emphasizes the importance of increasing tax awareness in building sustainable tax compliance.